Managing dryland forests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
international symposium on the integrated management of natural forests in the arid areas of western Africa, held in November 1998 in Ouagadougou, Burkina Faso